Inhibitory effects of Aphanizomenon flos-aquae constituents on human UDP-glucose dehydrogenase activity. (1st November 2016) - Scoglio, Stefano; Lo Curcio, Valeria; Catalani, Simona; Palma, Francesco; Battistelli, Serafina; Benedetti, Serena
Abstract: Objective : The purpose of this study was to investigate the in vitro inhibitory effects of the edible microalga Aphanizomenon flos-aquae (AFA) on human UDP-α-d -glucose 6-dehydrogenase (UGDH) activity, a cytosolic enzyme involved both in tumor progression and in phytochemical bioavailability. Methods : Both the hydrophilic and ethanolic AFA extracts as well as the constitutive active principles phycocyanin (PC), phycocyanobilin (PCB) and mycosporine-like amino acids (MAAs) were tested. Results : Among AFA components, PCB presented the strongest inhibitory effect on UGDH activity, acting as a competitive inhibitor with respect to UDP-glucose and a non-competitive inhibitor with respect to NAD + . In preliminary experiments, AFA PCB was also effective in reducing the colony formation capacity of PC-3 prostate cancer cells and FTC-133 thyroid cancer cells. Conclusions : Overall, these findings confirmed that AFA and its active principles are natural compounds with high biological activity. Further studies evaluating the effects of AFA PCB in reducing tumor cell growth and phytochemical glucuronidation are encouraged.